PERANAN GAYA KEPEMIMPtINAN TERHADAP KINERJA MANAJERIAL DENGAN VARIABEL MODERASI SISTEM AKUNTANSI MANAJEMEN, STRATEGI BISNIS DAN KETIDAKPASTIAN LINGKUNGAN - Sukmana, Purwo Hadi; Harymawan, Iman (Fakultas Ekonomi dan Bisnis Islam, 2018)
ABSTRACT The success of a leader can be seen from the ability of a leader to be the trigger he leads by creating conducive working conditions so as to increase progress and increase capacity which results in a positive influence on human resources led in running work in the direction of achieving organizational goals. This study uses moderating variables of management accounting systems, business strategies and environmental uncertainties that can encourage leadership styles for optimal managerial performance. This study uses hyphotheses testing study with a method of collecting data through questionnaires distributed to respondents managers at pharmaceutical distributors spread across Sidoarjo and Surabaya. This study resulted that leadership style had a significant effect on managerial performance, but for variable interactions (moderation) of business strategies, management accounting systems and environmental uncertainties did not provide a moderating effect on the relationship of leadership style to managerial performance. This is because pharmaceutical distributors are an agency that has an optimal business strategy and management accounting system. The environmental uncertainty of companies engaged in this sector also does not have a significant impact on the sustainability of the organization, because medical needs, whether medicine or medical devices, are a major need for the health unit and the Indonesian community, of course.Keywords: leadership style, business strategy, management accounting system, environmental uncertainty, managerial performance